2021
DOI: 10.1038/s41598-021-00735-3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular morbidities in postoperative colorectal cancer patients

Abstract: This retrospective observational study investigated the long-term prevalence of new-onset cardiovascular disease (CVD) and the predictive role of atherosclerotic plaque in the aorta and iliac arteries for CVD in postoperative colorectal cancer (CRC) patients who received surgical treatment between 2014 and 2015. CVD included coronary or cerebrovascular diseases which required treatment and new-onset CVD included peri-and postoperatively diagnosed CVDs or aggravated CVDs that required additional treatment durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The findings of this research are consistent with the existing literature on cardiovascular complications in CRC patients [2,48,49]. Moreover, we have furthered the understanding of oxidative stress and cardiovascular complications in patients with CRC, thus providing new clues for prevention and treatment.…”
Section: Implications For Future Researchsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this research are consistent with the existing literature on cardiovascular complications in CRC patients [2,48,49]. Moreover, we have furthered the understanding of oxidative stress and cardiovascular complications in patients with CRC, thus providing new clues for prevention and treatment.…”
Section: Implications For Future Researchsupporting
confidence: 89%
“…Recent epidemiological data shows that CRC has become a significant burden in terms of incidence and mortality rates [1][2][3][4]. Despite advances in diagnostic and treatment approaches, the overall survival rate of CRC patients remains relatively low, indicating the need for further improvement in management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The 10-year cumulative incidence of new-onset cardiovascular disease and CHF was 57.4 and 54.5% for patients with stage I–III CRC compared with 22 and 18% for the matched cohort without cancer, respectively ( p < 0.001) ( 7 ). Correspondingly, a Korean cohort study reported 141 (4.9%) patients who developed new-onset CVD among postoperative CRC patients ( 8 ). These studies raised the increasing concern of CV-related adverse events among CRC survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative chemotherapy is associated with an increased risk of CVD ( 7 , 8 ). Fluoropyrimidine is the backbone of chemotherapy in the adjuvant setting in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%